P 101 Quantitative Chemical Shift Spectroscopy (CSI) with respect to B0- and B1-inhomogeneities. Issue 10 (October 2017) - Baier, H.; Svatko, Z.; Spielmann, R.P.; Knörgen, M.
Abstract : Introduction: CSI is a method to visualize brain metabolism of, which may be important in the diagnosis of diseases like Alzheimer, dementia, brain tumors etc. Despite the fact that signal strength increases linearly with higher B0 -fields, there exist many confounding variables, which diminish the accuracy of quantitative measurements of a 3 T-device in relation to 1.5 T. Susceptibility artifacts caused by inhomogeneities in the B0 - and B1 -fields as well as digitalization artifacts represent a challenging obstacle to measure accurate quantitative values of metabolite concentrations in CSI. In this work we present measurements and numerical calculations of the influence of these artifacts on CSI. Materials and methods: Measurements were executed on a head phantom containing brain metabolites (NAA, Cr, Cho, mI, Glu). Spectra were analyzed by LCModel using basic data sets simulated by VeSPA-Simulation. Graphic results were plotted by Matlab-procedures. Results: The influence of confounding factors for CSI-measurements could be quantified. Software routines are given for graphical representation of B0 - and B1 -inhomogeneities. Furthermore, the influence of digitalization on the PSF (point spread function) for the measured phantom was reduced by a correction matrix.